2008
DOI: 10.1001/archinte.168.10.1049
|View full text |Cite
|
Sign up to set email alerts
|

Acute Coronary Syndrome

Abstract: Background: The effectiveness of therapy for an acute coronary syndrome (ACS) is dependent on patients' quick decision to seek treatment. We surveyed patients' level of knowledge about heart disease and self-perceived risk for a future acute myocardial infarction (AMI) in patients with documented ischemic heart disease. Methods: Patients (N=3522) had a mean age of 67 years, 68% were male, and all had a history of AMI or invasive cardiac procedure for ischemic heart disease. Data were gathered using a 26-item i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
9

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(27 citation statements)
references
References 24 publications
1
17
0
9
Order By: Relevance
“…Among these high-risk participants, 43% underestimated their risk for a future AMI (males 47%, females 36%). 35 …”
Section: Coronary Heart Disease Acute Coronary Syndrome and Angmentioning
confidence: 99%
“…Among these high-risk participants, 43% underestimated their risk for a future AMI (males 47%, females 36%). 35 …”
Section: Coronary Heart Disease Acute Coronary Syndrome and Angmentioning
confidence: 99%
“…Also, female gender, higher education, and health insurance status were predictive of higher scores. In a study of more than 3,000 participants with a history of ischemic heart disease, Dracup et al (2008), using a different scale, reported a mean CVD knowledge score of 71%. The mean knowledge score in our cohort, therefore, was fairly high considering that the cohort was younger and had a higher percentage of non-high-school graduates than other non-HIV studies.…”
Section: Discussionmentioning
confidence: 99%
“…Among these high-risk participants, 43% underestimated their risk for a future AMI (men 47%, women 36%). 40 …”
Section: Coronary Heart Disease Acute Coronary Syndrome and Angmentioning
confidence: 99%